(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study we examined the relationship between occupational stress and emotional intelligence among Degree College Teachers. We also explored the role of socio-demographic factors on occupational stress and emotional intelligence. Samples comprised of 200 college teachers, Karnataka, India (110 males and 90 females) between the age group of 28 to 60 years (mean age =46.7 years) randomly selected from Degree College Teachers affiliated by V.S.K. University. Bellary, India. Tools used for data collection were the (1) Emotional Intelligence Scale (Hyde, Pethe, and Dhar, 2002), (2) Occupational Stress Index (Srivastava and Singh, 1981) and (3) the Personal Information Schedule.Chosen after a comprehensive review of related literature. The samples were contacted individually by the researcher and data was collected through face to face interview. Data collection was spread over a period of one month. Mean, SD, ‘t’ test, and Pearson product moment correlation were the statistical analyses done. From the result we found that emotional intelligence and occupational stress were negatively and significantly related. We also found that socio-demographic variables such as, gender educational qualification, residential status, income and family type were not significant on influence both occupational stress and emotional intelligence. However age had a significant influence on occupational stress and emotional intelligence. However, age had a significant influence on emotional intelligence but was not significant for occupational stress.